Restauração florestal em área degradada por pastagem no Sul do Brasil - Webler, Caren Daiana Perius (2018)
Forest restoration is an important tool in restoring the ecological integrity of ecosystems and functions related to a natural landscape. However, restoring a degraded ecosystem, which aims to achieve high biological diversity and favor ecological processes, is a slow and complex task. The execution of a project demands commitment, because besides the damage to the vegetation, the degradation causes the soil impoverishment and the deterioration of the agents acting in the natural regeneration. The use of biological measures that promote the reconstruction of these environments is fundamental to the success of the restoration. In this context, the purpose of this study was to evaluate the effect of forest restoration techniques on an area with a Regosol degraded by livestock activity, considering the establishment of vegetation and the physical, chemical and biological parameters of the soil. The experiment was conducted in a randomized block design, using 4 blocks and 6 treatments, totaling 24 experimental units of 25 m² each. The restoration techniques tested were seed rain (CS), soil transposition (TS), artificial perches (PA), trunks and rocks (TR), planting of seedlings (PM) and control (C). The vegetation and the edaphic fauna were evaluated considering the abundance of individuals and the indices of wealth, diversity of Shannon and Pielou equability. Soil attributes, N and C contents, soil density, total porosity, micro and macroporosity, moisture in field capacity, available water, aggregate stability, water dispersed clay and flocculation degree were evaluated. The data were evaluated in the SASM-Agri software, version 8.2, using the ANOVA statistical test. To compare the means of treatments, the Scott-Knott test was used, considering a 5% level of significance. In the analysis of vegetation establishment, the highest abundance of individuals and the highest index of wealth, diversity and equability were recorded in TS. The TS treatment also obtained the highest levels and stocks of N and C. Soil density, total porosity and macroporosity presented significant differences between the averages in the layer of 0.00 to 0.05 m, where TS again presented the best behavior, with the lowest value of density and the highest values of total porosity and macroporosity. The highest percentage of aggregation was verified in the larger diameter classes, with the highest values of DMP and DMG recorded in CS in the layer of 0.00 to 0.10 m and in TS in the layer of 0.10 to 0.20 m. Treatment C showed the highest degree of flocculation. PM presented the greatest abundance of individuals of edaphic fauna. The highest values of diversity and equability were observed in TS. The results indicate that the forest restoration techniques used in this study are as efficient as the standard method conventionally used in restoration projects. Therefore, it can be concluded that the success of a forest restoration program depends on the use of means that stimulate ecological succession and facilitate the colonization of the area to be recovered.